HUBUNGAN SHIFT MALAM TERHADAP PENYAKIT REFLUKS GASTROESOFAGUS PADA PERAWAT DI RUMAH SAKIT UMUM PUSAT SANGLAH - Handayani, Putu Novi; Kumbara, Cokorde Istri Yuliandari Krisnawardani; Widiana, I Gde Raka; Merati, Ketut Tuti Parwati (E-Jurnal Medika Udayana; Vol 12 No 1 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i01.P14, 2023)
Gastroesophageal reflux disease is one of the most frequently diagnosed gastrointestinal diseases in the world with a prevalence that continues to increase every year. There are several studies state that night shifts can increase the risk of GERD. One group of workers who often undergo night shift rotation are nurses who work in hospitals. This study aims to determine the correlation between night shift work and gastroesophageal reflux disease among nurses. This study is an analytical study with a cross-sectional design. The data collection technique was carried out by purposive sampling by distributing questionnaires to 161 nurses on duty at Single Hospital which were divided into 85 Inpatient Installation nurses who worked night shifts and 76 Outpatient Nurses who worked morning shifts. This study found a significant correlation between night shift work and gastroesophageal reflux disease (p value = 0.013; Prevalence Ratio = 3; 95% Confidential Interval 1.18-7.84) by the chi square test. Furthermore, by the logistic regression analysis of night shift and GERD, the AOR (Adjusted Odd Ratio) was 3.61 with 95% CI (1.05-12.52) and other variable like age, gender, BMI and fast food consumption habits on GERD did not shown any significant result. There is a significant correlation between night shift work and gastroesophageal reflux disease. Nurses who undergo night shifts have a 3.61 times higher risk of experiencing GERD. Keywords : Night Shift Work, Gastroesophageal Reflux Disease, Nurse